2020
DOI: 10.1016/j.bbmt.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation in Congenital Erythropoietic Porphyria: Sustained Efficacy but Unexpected Liver Dysfunction

Abstract: Congenital erythropoietic porphyria (CEP) is a rare disease characterized by erosive photosensitivity and chronic hemolysis due to a defect of the enzyme uroporphyrinogen-III-synthase (UROS). To date, hematopoietic stem cell transplantation (HSCT) is the only curative therapy for the devastating early and severe form of the disease. We describe 6 patients with CEP treated with HSCT (3 of them twice after failure of a first graft) between 1994 and 2016 in our center, including 2 of the very first living patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
(25 reference statements)
3
25
0
Order By: Relevance
“…There may be residual UROS or FECH deficiencies in other non‐erythropoietic sites, as suggested by mildly persistently elevated TUP or TPP levels, which is seen in our cohort and others, however patients remain asymptomatic 4 . At time of publication, over 20 patients with CEP and nine patients with EPP have been reported (including our cohort) in the literature to have successfully undergone HSCT, with no reports of symptom recurrence 4,6–8,11–14 …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…There may be residual UROS or FECH deficiencies in other non‐erythropoietic sites, as suggested by mildly persistently elevated TUP or TPP levels, which is seen in our cohort and others, however patients remain asymptomatic 4 . At time of publication, over 20 patients with CEP and nine patients with EPP have been reported (including our cohort) in the literature to have successfully undergone HSCT, with no reports of symptom recurrence 4,6–8,11–14 …”
Section: Discussionsupporting
confidence: 52%
“…4 At time of publication, over 20 patients with CEP and nine patients with EPP have been reported (including our cohort) in the literature to have successfully undergone HSCT, with no reports of symptom recurrence. 4,[6][7][8][11][12][13][14] HSCT effectively corrects the defective bone marrow heme pathway in patients with erythropoietic porphyrias. The risks of HSCT have traditionally outweighed the benefits for the majority of patients with erythropoietic porphyrias, but contemporary strategies have made transplants safer.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, CEP can be difficult to diagnose with a reported median age of diagnosis of 7 months with typical red urine, CEP skin lesions and hemolytic anemia appearing at median age of 1, 2, and 8 months, respectively. 21 Martinez Perinado et al 12 reported an early onset case of CEP who presented with severe post-delivery manifestations and underwent a matched unrelated HSCT at age 7 months. As CEP is a rare condition, a multidisciplinary evaluation led by the responsible pediatrician is necessary for early diagnosis and genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports of successful HSCT in the treatment of CEP also described a similar situation, notably a recent study describing near-normal biological levels of porphyrins 25 years after HSCT. 21 The remaining elevated porphyrin levels, despite HSCT, might reflect the porphyrin production by nonerythroid tissues. Indeed, UROS deficiency is still present in nonerythroid tissues (i.e., liver cells) leading to a persistent accumulation of porphyrins despite full replacement of erythroid tissues with HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation